USE OF CREATIVE WORK IN CLASSES ENGLISH AS A MEANS OF QUALITY IMPROVEMENT KNOWLEDGE OF FUTURE SPECIALISTS (Pedagogy of Higher and Secondary Education, 2008)
In article problems of use of creative work of students on employment on English language in the higher school, as the way of quality of knowledge are considered.